Prime Minister’s Decree No. 3093 Of The Year 2010 Concerning The Formation Of The Higher Consultative Council For Vocational Safety And Health And Ensuring Labour Environment Security = قرار رئيس مجلس الوزراء رقم 3093 لسنة 2010 بشأن تشكيل المجلس الاستشارى الأعلى للسلامة والصحة المهنية وتأمين بيئة العمل - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.